The Digital Person : Technology and Privacy in the Information Age. - Solove, Daniel J. (Ex Machina: Law, Technology and Society Series., 2004)
Seven days a week, twenty-four hours a day, electronic databases are compiling information about you. As you surf the Internet, an unprecedented amount of your personal information is being recorded and preserved forever in the digital minds of computers. For each individual, these databases create a profile of activities, interests, and preferences used to investigate backgrounds, check credit, market products, and make a wide variety of decisions affecting our lives. The creation and use of these databases--which Daniel J. Solove calls "digital dossiers"--Has thus far gone largely unchecked. I.